Bioscaffold materials resist infection and promote bone defect repair by regulating neutrophil function - Zhou, Jingyu; Xiong, Shilang; Liu, Shiwei; Zhou, Zhigang; Liu, Min; Xi, Hanrui; Kong, Weihao; Zhou, Jianguo; Xiong, Long (Frontiers in Bioengineering and Biotechnology, 2025)
Infectious bone defects frequently encounter challenges related to bacterial infection and bone integrity. Neutrophils, being the initial responders to sites of inflammation, employ multiple mechanisms to eradicate bacteria, including phagocytosis, degranulation, the formation of neutrophil extracellular traps (NETs), and the oxidative respiratory burst. As a critical component of the human immune system, neutrophils play a pivotal role in modulating the inflammatory response, influencing the processes of osteogenesis and osteoclastogenesis, and impacting fracture healing. In the field of bone tissue engineering, the optimization of the chemical composition and morphology of scaffold materials can effectively modulate neutrophil behavior, thereby enhancing the antibacterial properties and osteogenic potential of the scaffolds. These approaches offer innovative strategies for designing bone tissue engineering scaffolds capable of regulating immune responses, with the potential to achieve improved clinical outcomes in future therapeutic applications.